Gamification and Communicative Language Teaching in an English Program for Underprivileged Children - Dominggus Florensius; Bahing; Richard Ferry Nugraha; Don Evan Hernando; Susanty (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
This study examines the implementation and its impact of Communicative Language Teaching (CLT) approach and strategies with the EFL students’ perception towards English language learning. This study was conducted in the English language teaching program for children at the Imanuel Palangka Raya Orphanage, Central Kalimantan. The limited number of competent English teachers in the orphanage environment is the main background for the implementation of this educational intervention program. Using a descriptive qualitative method, data were collected through participatory observation, informal interviews, and documentation during five meetings involving 20 participants from the elementary and junior high school levels. The results showed that the integration of CLT and gamification effectively increased participants' engagement, motivation, and courage to communicate in English. Game elements such as activity card challenges, guess the picture quizzes, and singing competitions between groups have been proven to be able to create a fun, interactive, and conducive learning atmosphere for the development of participants' English skills. This study confirms that the game-based interactive learning approach is very relevant to be applied in non-formal education environments, especially for groups of children who have had minimal access to quality and equitable English language teaching.